2017
DOI: 10.1523/jneurosci.2873-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex KCa2 Channels Regulate mGlu5-Dependent Plasticity and Extinction of Alcohol-Seeking Behavior

Abstract: Identifying novel treatments that facilitate extinction learning could enhance cue-exposure therapy and reduce high relapse rates in alcoholics. Activation of mGlu receptors in the infralimbic prefrontal cortex (IL-PFC) facilitates learning during extinction of cue-conditioned alcohol-seeking behavior. Small-conductance calcium-activated potassium (K2) channels have also been implicated in extinction learning of fear memories, and mGlu receptor activation can reduce K2 channel function. Using a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…Following restraint stress, this M 1 /mGlu 5 -dependent LTD remained intact (Figure 2d). Finally, we assessed the ability of mGlu 5 activation to inhibit the function of SK channels (Cannady et al, 2017). We evaluated SK channel function by measuring Q AHP and found no basal difference following restraint stress (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Following restraint stress, this M 1 /mGlu 5 -dependent LTD remained intact (Figure 2d). Finally, we assessed the ability of mGlu 5 activation to inhibit the function of SK channels (Cannady et al, 2017). We evaluated SK channel function by measuring Q AHP and found no basal difference following restraint stress (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we identified a DMR that maps to an ion channel gene previously implicated in excessive drinking, ethanol-seeking behaviors, and ethanol-induced plasticity of intrinsic excitability (6,10,11,13,17). Our analysis identified a DMR that spans exon 1 and part of intron 1 of monkey and mouse KCNN3 in a region containing CpGs that are highly conserved across species.…”
Section: Discussionmentioning
confidence: 82%
“…Next, 1.25 μl of cDNA was pre-amplified using 1 μl of PreAmp master mix, 0.5 μl of pooled primers (at 500 nM) and 2.25 μl of RNase-free water. The Pre-Amplification conditions were 95 C for 2 min, followed by 10 cycles at 95 C for 15 s and 60 C for 10 μl Exonuclease I (20 Units/ml) and 1.4 μl of RNase-free water. The reactions were incubated at 37 C for 30 min followed by 80 C for 15 min.…”
Section: Rna Isolation and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the extensive repertoire of synaptic plasticity expressed by medial PFC synapses is sensitive to various regimen of exposure to drugs of abuse (Kassanetz et al 2010; Cannady et al, 2017, Renard et al, 2016; Lovelace et al, 2015; van Huijstee and Mansvelder, 2014) we assessed a second type of plasticity in the PFC which is frequently related to endophenotypes of neuropsychiatric disorders (Labouesse et al 2016; Manduca et al, 2017; Neuhofer et al, 2015; Iafrati et al, 2016; Thomazeau et al, 2014), the NMDAR-dependent LTP (NMDAR-LTP). NMDAR-LTP was ablated in adult male rats while pubescent males were spared.…”
Section: Resultsmentioning
confidence: 99%